TANTANGAN DAKWAH DI DAERAH PERKEBUNAN KARET DAN KELAPA SAWIT TRANSMIGRAN SUMBER MAKMUR PALEMBANG - Mar’atus Sholehah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2018)
The study of the challenges of da'wah in the Sumber Makmur Palembang rubber and oil palm plantation area has not been done much by the researchers. The focus of the problem to be explored is the response and the pioneering paradigm of the pioneers of the Sumber Makmur religion towards cultural and religious diversity, as well as how the da'wah strategies they developed in maintaining inter-faith harmony. Data from the research shows that the views and attitudes of the pioneers of religion in Sumber Makmur towards cultural diversity and religion, generally refer to the paradigm of respect and respect for each other. To find an effective da'wah strategy and solve socio-religious problems of the transmigration community in Sumber Makmur village. In order to realize an effective Islamic da'wah strategy so that it can change the condition of the community, it must be encapsulated in the components of da'i, such as da'I, da'wah material, methods of da'wah, media and the presentation of da'wah in accordance with the conditions of the transmigration community. Therefore the strategy of Islamic da'wah in transmigration areas must not be carried out by one institution, but must involve various parties. Obviously the government, da'wah bodies, Islamic organizations, rich people and the da'I themselves, should cooperate and work together in smoothing out the activities of da'wah. Da'wah in Sumber Makmur village focuses on improving the economy, education, health, transportation facilities, and other facilities.